Respon Siswa Terhadap Media Dakon Matika Materi KPK dan FPB pada Siswa Kelas IV di SD/MI Lamongan - ummu khairiyah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2019)
This research aimed to know the response of the students against the media learning material on the matika dakon KPK and FPB in class IV. The research methods apply in this research is descriptive research. The subject of this research is 25 students of class IV SDN Tenggerejo 2 Kedungpring Lamongan. Research instrument used is a questionnaire form. The criteria of response consists of 5 indicators are judgments, interest, motivation, satisfaction, and response. The analysis of the questionnaire shows that the average value of student response against media dakon matika is very positive with a percentage amounting is 93.6%